Environmental, Social & Governance (ESG) Implementation Strategy in Mining Companies with Design Thinking Method - Mgs Deni Trisna Jaya; Mahendra Wardhana (Publikasi Indonesia, 2025)
The mining industry plays an important role in economic development, but its operations often have adverse environmental and social impacts and many companies are only concerned with profit. So it is important to apply ESG (Environmental, Social, Governance) principles to companies to create a sustainable business. This thesis examines the application of ESG in PT. X as a mining company. This research is qualitative research and uses descriptive analysis with the design thinking method. Observations and interviews were conducted at PT. X and using an informant from the management of PT. X. This research also aims to find effective strategies in the implementation of ESG in strengthening business sustainability in PT. X by using indicators from the ESG Reporting Guide that uses the Global Reporting Standard (GRI) in the mining sector. Based on the results of the analysis, it was found that the implementation of ESG in PT. X has achieved a percentage of 95% of the GRI Coal standard. There is one indicator that has not been implemented, namely the water and effluent indicators on the environmental aspect. Alternative strategies developed with design thinking methods are in the form of making rainwater catchment ponds, remote control waterfill, and automatic sprayer.